The Validity Of Inter-Religious Marriages: A Fiqh And Positive Law Perspective - Maria MT Manurung; M. Iqbal Irham (AT-TAFAHUM: Journal of Law, 2019)
The practice of interfaith marriage among Muslims in Indonesia is still prevalent in society. This phenomenon has given rise to various controversies and debates from religious, social, psychological, and legal perspectives. This paper will discuss the validity of interfaith marriage in Indonesia from the perspective of Islamic jurisprudence and positive law. The method used is normative legal research with library research as the data source. The data is then collected, processed, analyzed, and presented qualitatively. The results of the study conclude that Islamic jurisprudence scholars agree that marriage between a Muslim man and a non-Muslim polytheist woman is prohibited. This opinion refers to the verses of QS 2:221, QS 60:10, QS 5:5, and considerations of public interest. In the legal context in Indonesia, the Compilation of Islamic Law (KHI) regulates the prohibition of interfaith marriage. Meanwhile, the Marriage Law does not clearly regulate the permissibility of interfaith marriage, thus leaving room for differing legal interpretations in society. The Population Administration Law and several court rulings have opened the door to recognizing interfaith marriages, making them valid, registered, and recognized by the state. However, this development led to the birth of Supreme Court Circular Letter No. 2 of 2023, which prohibits courts from granting permits for registering interfaith marriages. Interfaith marriages not registered with an official institution have no legal status in the eyes of the state. Consequently, such marriages are not administratively recognized.